Is State-Wise Healthcare Budget Allocation Consistent With the Disease Burden in India? A Quinquennial Account (2015–2019) - Bagepally, Bhavani Shankara; Kumar, S. Sajith; Sasidharan, Akhil (Frontiers in Public Health, 2022)
Introduction: Evidence-based resource allocation may help to achieve health gains in resource-limited settings like India. Understanding healthcare expenditure and corresponding disease-burden could provide insights to plan optimal allocation of limited resources. Hence, we aimed to investigate status and trends of state-wise healthcare budget allocation and corresponding disease-burden. Methods: We retrieved state-wise healthcare budget allocation information in India for the years 2015 to 2019. Corresponding state-wise disability-adjusted-life-year (DALY) estimates from Global Burden of Disease Studies, injuries, and Risk Factors Study study was used to measure disease burden. The allocated budget (in rupees) per DALY was calculated for overall, communicable, and non-communicable diseases (NCDs). Descriptive statistics, correlation and graphical representations were used to identify and evaluate the trends and relationships between state-wise health budget allocation and disease burden. Results: Allocated budget per DALY in 2019 was highest for Goa (₹34,260 or US486·66) and lowest for Bihar (₹2,408 or US 34·20). Smaller, less populous states had higher budget allocations per DALY than larger states. Health budget allocation had inverse relationship with infectious diseases and linear relationship with NCDs. Most state-wise budget allocations, as well as disease burden, increased over years except for Assam, Karnataka and Himachal-Pradesh. Also, such trends are not similar for injuries and NCD burden. Discussion: The health budget allocation is variable across states as well as between infectious and NCDs. The current increase in the allocated budget is incongruent with increasing disease burden. There is a need for rapid expansion of healthcare resource allocation guided by evidence in India.